THE TRANSFER OF SESAME STREET TO LATIN AMERICA - MAYO, JOHN K. and E OLIVEIRA, JOAO BATISTA ARAUJO and ROGERS, EVERETT M. and GUIMARAES, SONIA DANTUS PINTO and MORETT, FERNANDO (Communication Research, 1984)
Here a package of communication technologies, embodied in Sesame Street (a tremendously popular and effective children's TV series) is traced during its transfer from the United States to Mexico and Brazil. The Mexican and Brazilian programs attracted huge audiences of children and adults throughout Latin America, yet the coproductions of Plaza Sésamo and Vila Sésamo ceased after only two or three seasons, and little long-range effect is discernible today in Latin American children's television. Explanations for the short-run success and long-run failure of the transfer of Sesame Street to Latin America can be found in the nature of the supplier-receiver relationships, and in the emphasis on product transfer rather than process modification and adjustment.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwODQwMTEwMDIwMDg